IMPROVING THE CONCEPTUAL FRAMEWORK FOR ENHANCING THE COMPETITIVENESS OF COMMERCIAL BANKS IN EMERGING FINANCIAL MARKETS: THE CASE OF UZBEKISTAN - Matluba M. Abdurakhmanova (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2026)
This article examines theoretical and methodological approaches to enhancing the competitiveness of commercial banks in emerging financial markets. Particular attention is paid to the transformation processes in the banking sector of Uzbekistan. An improved conceptual model of bank competitiveness is proposed, incorporating digitalization, institutional changes, and market liberalization. The findings of the study may be used in the development of banking strategies and the improvement of financial policy.